Leafhopper, Amrasca biguttula biguttula (ishida): An Emerging insect pest on sunflower: Leafhopper, Amrasca biguttula biguttula (ishida): An Emerging insect pest on sunflower - VIJAYKUMAR N GHANTE; POORNIMA; M R UMESH; VIKAS KULKARNI (Journal of Oilseeds Research, 2023)
The present experiment was conducted to know the seasonal incidence of leafhopper, A. biguttula biguttula on sunflower. The significant and negative correlation was observed between nymphal population and minimum temperature, while bright sunshine hours showed a significant and positive correlation. However, there was no significant and positive correlation between leafhopper population and Rainfall. Whereas, the relation was negative and non-significant with maximum temperature, morning relative humidity and evening relative humidity.